Testing the reported long-term advantages of protein-fortified human milk in very low birth weight neonates - Biasini, Augusto; Neri, Erica; Stella, Marcello; Malaigia, Laura; Mariani, Elisa; Rizzo, Vittoria; Agostini, Francesca (Frontiers in Pediatrics, 2024)
Preterm infants are at-risk for extrauterine growth restriction and downward percentile-crossing between birth and discharge. Increased energy and protein intake through fortification of human milk during the first weeks of life has been associated with improved short-term growth and better developmental outcomes. The aim of this study was to evaluate whether these benefits persist up to children school age. The study was designed as an observational study. During hospitalization, 22 very low birth weight preterm infants were fed with increasing protein fortification of human milk (protein supplemented group, PSG). As a control group (CG), 11 preterm infants were fed with standard nutrition regimen. At children school age (9-11 years), we assessed anthropometric data (weight, height, BMI), global health (renal function), and specific psychological outcomes (Child Behavior Checklist 6-18). A global homogeneity between CG and PSG groups emerged: we found no significant differences in weight, height, and BMI, nor in internalizing symptom outcomes (all ps >0.05). However, mothers reported significantly higher externalizing symptoms for the PSG infants compared to CG infants. Therefore, neonatal enteral protein supplementation in very low birth weight preterm infants did not lead to positive nor adverse consequences in long-term assessment, suggesting that benefits are restricted to the neonatal term and first years of age.